The Influence of Performance Improvement Strategies and Work Discipline on the Professionalism of Lecturers at PGRI Jombang University - Ferdi Andri Asmawan, Yudhi (Terbuka Journal of Economics and Business, 2024)
Improving the quality of higher education is impossible without improving the quality of its lecturers. Improving lecturer performance to support the implementation of quality education. Higher education as an educational unit that has the main task of producing quality human resources. The purpose of this study is to determine the description of the variables of lecturer performance improvement strategies, work discipline, and lecturer professionalism. To determine and analyze the influence of lecturer performance improvement strategies partially on lecturer professionalism. To determine and analyze the influence of work discipline partially on lecturer professionalism. To determine and analyze the influence of lecturer performance improvement strategies and work discipline simultaneously on lecturer professionalism. The method used in this study is quantitative analysis method. The results of the study indicate that the description of the variables of lecturer performance improvement strategies, work discipline, and lecturer professionalism are normally distributed. Partially, the performance improvement strategy variable has a significant effect on lecturer professionalism. The work discipline variable has no significant effect on lecturer professionalism. The lecturer performance improvement strategy variable has a significant effect on lecturer professionalism, while the work discipline variable has no significant effect on lecturer professionalism.